Heavy Metal Concentrations in Razor Clam (Solen marginatus, Pulteney, 1799) and Sediments from Izmir Bay, Aegean Sea, Turkey - Elif Çağrı Taş; Uğur Sunlu (Turkish Journal of Agriculture: Food Science and Technology)
This study was carried out to determine the concentrations of some heavy metals (Cd, Cu, Pb, Zn, Cr and Fe) in Solen marginatus (Pulteney, 1799) and sediments in the middle region of Izmir Bay. Metal concentrations in S. marginatus vary in the one-year period between summer 2005 and summer 2006. The order of accumulation of metal concentrates in soft tissue of razor clam was determined as Cd < Pb < Cr< Cu < Zn < Fe. Metal accumulations in the soft tissue of S. marginatus were compared with Provisional Tolerable Weakly Intakes (PTWI) and Provisional Tolerable Daily Intakes (PTDI) for human consumption. The results show that the maximum concentrations of metals were markedly below the limits of the FAO (Food and Agriculture Organization), WHO (World Health Organization) and TFC (Turkish Food Codex) for human consumption. The order of the metal concentrations detected in the sediment samples was Cd < Pb < Cu< Cr < Zn < Fe. In this study, the maximum heavy metal values determined in the sediment are below the criteria values of the stated for international sediment quality guidelines in the NOAA (The National Oceanic and Atmospheric Administration), OMEE (The Ministry of Environment and Energy of Ontario), ANZECC (The Australia and New Zealand Environmental on Conservation Council), CCME (The Canadian Council of Ministers of Environment). There was a statistically significant but weak correlation between concentrations of Cu and Cr in sediment and S. marginatus. The significant correlations have shown that Solen species can be used as a bioindicator species, such as mussels due to their ability to accumulate heavy metals.